2015
DOI: 10.1097/mpg.0000000000000895
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C in Children Co‐infected With Human Immunodeficiency Virus

Abstract: The effect of HIV co-infection on HCV-related disease was clear with most studies indicating that HIV accelerates HCV progression and reduces the efficacy of the available anti-HCV therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…Among children, mother to infant is by far the most common mode of transmission of HIV/HCV co‐infection, ranging from 4% and 10% according to reports from the late 90s in Europe, before generalization of combined antiretroviral treatment (ART) . As a result, the population of vertically HIV/HCV–co‐infected patients grows up in the presence of two complex chronic infections, whose long‐term effects on chronic inflammation, immune dysfunction and liver disorders have been barely explored …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among children, mother to infant is by far the most common mode of transmission of HIV/HCV co‐infection, ranging from 4% and 10% according to reports from the late 90s in Europe, before generalization of combined antiretroviral treatment (ART) . As a result, the population of vertically HIV/HCV–co‐infected patients grows up in the presence of two complex chronic infections, whose long‐term effects on chronic inflammation, immune dysfunction and liver disorders have been barely explored …”
Section: Introductionmentioning
confidence: 99%
“…However, the natural history of HCV infection shows a nonlinear progression to liver disease that can accelerate with the duration of the infection and/or ageing that leads to cirrhosis in approximately 16% of patients over a 20‐year follow‐up period . However, studies including co‐infected children and adolescents are limited and remain controversial, as histopathological data are scarce, and some studies have reported mild liver fibrosis among co‐infected children . A recent multicentre study using transient elastography has described that 14.5% of vertically HIV/HCV–co‐infected children progress to advanced fibrosis at a median age of 17 years…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 The incidence of spontaneous HCV clearance varies in childhood depending on virus genotype and figures from 7.5% to 25% have been quoted in the literature. 1012 However, in the presence of HIV coinfection, the likelihood of spontaneous clearance is much reduced in children 13 as in adults. 14 …”
mentioning
confidence: 99%